MODEL PENGEMBANGAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL - Kasinyo Harto (IAIN Ponorogo, 2014)
Abstract: This study aims to discover principles of and philosophical basis for multicultural Islamic religious education. This study is important due to ineffective application of Article 13A of National Education System Law that could endanger national education and unity of the nation. This is a library research that analyzes the Qur’an, hadist and scholarly views to formulate basic principles for multicultural Islamic education. The results of this formulation are used to compose curriculum, syllabus, teachers’ and students’ competence, model of learning and evaluation. This study argues that approaches to religious learning having been applied so far in schools need to be reformulated and accorded to the multicultural context of Indonesian society because they tend to create intolerant, exclusive and egoistic students and emphasize personal piety. Education should not only teach students how to think critically but also how to live side by side with others peacefully. This idea must be included in learning processes so multiculturalism and are applied through such processes.